Identification of candidate chemosensory genes in Bactrocera cucurbitae based on antennal transcriptome analysis - Wang, Jing Jing; Ma, Chao; Yue, Yang; Yang, Jingfang; Chen, Li Xiang; Wang, Yi Ting; Zhao, Chen Chen; Gao, Xuyuan; Chen, Hong Song; Ma, Wei Hua; Zhou, Zhongshi (Frontiers in Physiology, 2024)
The melon fly, Bactrocera cucurbitae (Coquillett) (Tephritidae: Diptera), is an invasive pest that poses a significant threat to agriculture in Africa and other regions. Flies are known to use their olfactory systems to recognise environmental chemical cues. However, the molecular components of the chemosensory system of B. cucurbitae are poorly characterised. To address this knowledge gap, we have used next-generation sequencing to analyse the antenna transcriptomes of sexually immature B. cucurbitae adults. The results have identified 160 potential chemosensory genes, including 35 odourant-binding proteins (OBPs), one chemosensory protein (CSP), three sensory neuron membrane proteins (SNMPs), 70 odourant receptors (ORs), 30 ionotropic receptors (IRs), and 21 gustatory receptors (GRs). Quantitative real-time polymerase chain reaction (qPCR) was used to validate the results by assessing the expression profiles of 25 ORs and 15 OBPs. Notably, high expression levels for BcucOBP5/9/10/18/21/23/26 were observed in both the female and male antennae.Furthermore, BcucOROrco/6/7/9/13/15/25/27/28/42/62 exhibited biased expression in the male antennae, whereas BcucOR55 showed biased expression in the female antennae. This comprehensive investigation provides valuable insights into insect olfaction at the molecular level and will, thus, help to facilitate the development of enhanced pest management strategies in the future.